Short Seller Influence on Firm Growth: A Threat Rigidity Perspective - Shi, Wei; Connelly, Brian L.; Cirik, Kubilay (Academy of Management Journal, 2018)
Whereas most investors seek to maximize their investment, there are some who profit from downward stock price movement. Engaging in such behavior is called "short selling," and it has increased considerably among publicly traded North American firms in recent years. This study builds on threat rigidity theory to develop arguments about the behavioral consequences of short sellers. We theorize that, when firms have a high level of short interest, managers adopt a defensive stance by halting new growth initiatives and limiting the range of growth modes in which they participate. We also suggest that managers' ability to process information and exercise control moderate these main effects. Specifically, we argue that managers will be less reactionary when firms have high absorptive capacity, possess high board centrality, maintain sufficient financial slack, and are well regarded by the media. Results largely support our theory, as we show that short sellers can have a profoundly deleterious effect on firm growth prospects.